The Influence of Transformational Leadership and Work Motivation on Employee Performance: Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Karyawan - Kurniadi K. Hasan (Institute of Educational, Research, and Community Service, 2023)
This study aims to determine the effect of transformational leadership and work motivation on the performance of employees of the General and Financial Bureau of Gorontalo State University, both partially and simultaneously. The approach in this research is quantitative. This research uses a survey method with a research design in the form of causality and a quantitative approach. The data analysis technique used is multiple regression. The results showed that (1) Transformational leadership has a positive effect on employee performance at the General and Financial Bureau of Gorontalo State University with a coefficient of determination of 29.70%. (2) Work motivation has a positive effect on employee performance at the General and Financial Bureau of Gorontalo State University with a coefficient of determination of 29.72%. (3) Transformational leadership and work motivation together have a positive and significant effect on employee performance at the General and Financial Bureau of Gorontalo State University with a coefficient of determination of 59.42%. While the remaining 40.58% can be explained by other variables not examined in this study such as remuneration variables, intellectual intelligence, emotional intelligence, spiritual intelligence of employees and employee career development